Pemahaman Islam dan Dampaknya terhadap Keharmonisan dan Keragaman Indonesia : Analisis Kritis terhadap Publikasi Jurnal Tahun 2010 sampai 2020 - Sardjana Orba Manullang; Mardani Mardani; Prasetyono Hendriarto; Aslan Aslan (Al-Ulum, 2021)
This article discusses the correct understanding of Islam that will impact harmony and the development of life in the Unitary State of the Republic of Indonesia. This article also wants to gain a deeper understanding of the above understanding through the findings of socio-religious and civic studies and their impact on community harmony. This study collects data from online publications, and then we analyze it by involving a careful coding system. Not to forget the critical evaluation and interpretation of the data we obtained to obtain findings that we believe are appropriate to answer all the problems we pose in this study of religion and citizenship. From the results of the discussion and interpretation with a phenomenological approach, finally, this study can conclude that citizen harmony occurs when citizens have and live religious understanding objectively and correctly to build more harmonious relationships in a country that adheres to diversity. The results of this study are beneficial for many parties for the sake of increasing Islamic brotherhood and the unity of Indonesian citizens.